أثر التسويق الإلكتروني على تطوير الخدمات المصرفية البنكية: دراسة ميدانية على البنوك الحكومية والخاصة بمحافظة كفر الشيخ - البلقاسي، منال صبحي علي Albelqasi, Manal Subhi Ali (جامعة المنصورة - كلية التجارة, 2017)
يهدف البحث إلى دراسة اثر التسويق الإلكتروني بمؤثراته وإيجابياته المتعددة على تطوير الخدمات المصرفية البنكية مثل السحب والإيداع والقروض والبطاقات الائتمانية وتحقيق أعلى مستوي من رضاء العملاء عن جودة الخدمة المقدمة وهل تفي تلك الخدمة بتوقعات العملاء من حيث الجودة والفاعلية والسرعة والسهولة وجودة التعامل والتكلفة والإعلان والأمان وغيرها أم لا. ، وللتحقق من هدف البحث استخدمت الباحثة أداة الاستبيان كأداة أساسية لقياس استجابات عينة البحث وهي عينة عشوائية من عملاء البنوك قوامها (٤٠٠) مفردة ممن يتعاملون مع البنوك الحكومية والخاصة بمحافظة كفر الشيخ خلال عام ٢٠١٦ مع التركيز على البنوك الخاصة لمعرفة المزايا التنافسية التي يمتلكها كل بنك وتميزه عن غيره وما هي الأسباب التي يستطيع بها البنك الحفاظ على عملاءه الحاليين وجذب عملاء جدد من خلال دراسة تأثير التسويق الإلكتروني على سنوات التعامل مع البنك وتوفر قاعده معلومات ودرجة المان والسرية وعدد مرات الزيارة البنكية والمزيج التسويقي للخدمات البنكية باستخدام المنهج الوصفي التحليلي. ، توصل البحث إلى أهمية التسويق الإلكتروني في تحسين جودة الخدمات البنكية وتحسين الوضع التنافسي بين البنوك لصالح البنوك التي تستخدم التسويق الإلكتروني لخدماتها، تحسين مستوى رضا العملاء وتوقعاتهم عن جودة الخدمة المقدمة، كما توصل البحث إلي عدم تأثير التسويق الإلكتروني للخدمات المصرفية البنكية على تخفيض تكلفة الخدمة المقدمة الكترونيا إلى حد كبير، كما لا يؤثر عدد مرات التعامل مع البنك في مستوى رضاء العملاء عن جودة الخدمة المقدمة، أيضا يؤثر التسويق الإلكتروني بفاعلية على المزيج التسويقي للخدمات المصرفية البنكية والوضع التنافسي لقطاع البنوك الخاصة. ، توصي الباحثة باستخدام مفهوم التسويق الإلكتروني لتطوير الخدمات المصرفية البنكية لتقديم خدمة بنكية متميزة تحافظ على عملاء البنك الحاليين وتستقطب عملاء جدد كما توصي بتفعيل خدمات الصراف الألي للإيداع لأنه من المزايا التي تحدد بقاء العميل بالبنك والتركيز على جميع مراحل المزيج التسويق للخدمات البنكية.
The aim of the study is to study the impact of e marketing on the development of bank banking services such as withdrawals, deposits, loans and credit cards, and achieve the highest level of customer satisfaction and study how these services meet customer expectations in terms of quality and effectiveness speed and ease. The researcher used the questionnaire as a basic tool to identify the opinions and suggestions of a random sample of 400 bank customers who deal with public and private banks in Kafr El-Sheikh Governorate in 2016. The focus was on private banks to know the competitive advantages that each bank has. The study aims at identifying the effect of the factors of the number of years of dealing with the bank, the number of bank visits, etc., and how electronic marketing affects the settlement mix. S banking services. The research found the importance of e marketing in improving the quality of banking services and improving the competitive situation between banks for the benefit of the banks that use e marketing for their services, which can maintain existing customers and attract new customers by improving the level of customer satisfaction and expectations about the quality of service provided. The electronic marketing of banking services to reduce the cost of the service provided electronically to a large extent, and does not affect the number of times dealing with the bank in the level of customer procurement for the quality of service provided, also affects the electronic marketing effectively on foe Internet The marketing of banking services and foe competitive situation between foe government and private banking sector, where each type of bank has certain services and criteria that support its competitive position among the corresponding banks. The researcher recommends foe use of foe concept of electronic marketing to develop banking services to provide a distinct banking service aimed at maintaining foe current customers of foe bank and attracting new customers, especially with foe multiplicity of banks and spread and recommends the activation of ATM services for deposit because of the advantages that determine the survival of the bank and also recommends focusing on all stages Marketing mix for banking services.
Keywords: التسويق الإلكتروني -- الخدمات المصرفية -- الصيرفة الالكترونية -- رضا العملاء -- البنوك المصرية